(untitled) (Journal of Partial Differential Equations, 2023)
In this paper, we study the existence of "weak solution" for a class of p(x)-Kirchhoff type problem involving the p(x)-Laplacian-like operator depending on two real parameters with Neumann boundary condition. Using a topological degree for a class of demicontinuous operator of generalized (S_+) type and the theory of the variable exponent Sobolev space, we establish the existence of "weak solution" of this problem.